Analysis of the paper: “Mollusks of Cocos Island” (1935) by Paul Biolley from the Social History of Science. - Díaz Bolaños, Ronald Eduardo (2020)
Introduction: The paper “Moluscos de la Isla del Coco” (Mollusks of Cocos Island) published in the Revista del Colegio Superior de Señoritas (1935) is the translation to Spanish of one of the last works of Paul Biolley Matthey (1862-1908), Swiss naturalist that lived in Costa Rica. This article was one product of a malacological research carried out during a scientific expedition organized by the ‘Instituto FísicoGeográfico Nacional de Costa Rica’ (IFGN) in 1902 to Cocos Island, at a time when the country claimed its sovereignty both in this territory. Objective: To analyze the contributions of the article “Moluscos de la Isla del Coco” from the Social History of Science approach. Methods: Most of the researches that have applied this approach in Costa Rica analyze processes of institutionalization of scientific disciplines. The methodology used in these works was very useful for the analysis of the Biolley article, together with the information of historical data provided by other texts about Cocos Island and the development of scientific research in Costa Rica from a temporal perspective. In addition, tables were made to synthesize the classification of the species and genera studied by Biolley in Cocos Island to identify their provenance and the habitat in which they lived. Results: This study of Biolley constitutes a text of interest from the point of view of the Social History of Science, due to the descriptions it offers of the physical conditions of the territory of Cocos Island, of the different species of mollusks located in them and to the exchange of information with national and foreign scientists that show the participation of Biolley in scientific networks. Conclusions: The analysis of the information with the Social History of Science approach, concludes that the compilation of the flora and fauna permits a greater knowledge of the natural resources of the explored territories, in order to colonize them and integrate them into the economic dynamics of the Central Valley of Costa Rica. However, attempts colonize Cocos Island failed given the distance between this and the continent, in addition to the topographic conditions that prevent the permanent establishment of human populations and their productive activities.